Why female students of undergraduate level got married in middle of their study: A study on university female students in Dhaka - Khatun, Mst Amina; Islam, Sirajul; Rakib, Majbaul Islam; Nipa, Tanjina Akter (International Journal of Asian Social Science, 2025)
Bangladesh exhibits one of the highest rates of marriage among undergraduate female students in South Asia. A significant portion of the nation’s population consists of young women who are essential to the country’s workforce; therefore, the issue of underage marriage must be addressed appropriately. Researchers collected data from 250 respondents across five universities in Dhaka city, which included both private and public institutions. A questionnaire was developed to gather information on personal details, economic factors, social influences, religious beliefs, personal motivations, and the impact of undergraduate female students’ marriages on their academic performance. Cross-sectional regression analysis was utilized in this study. The independent variables included social reasons (SR), religious reasons (RR), personal reasons (PR), and economic reasons (ER), while the dependent variables were family study conflict (FSC) and academic performance (AP). The findings indicate that religious reasons (RR) play a significant role in the marriage of undergraduate female students in Bangladesh. This phenomenon has a notably adverse effect on the academic performance of married female students at the undergraduate level. In addition to the existing laws, increasing awareness among the populace could help eliminate such issues in Bangladesh.